The Effect of Technology on Student’s Motivation and Knowledge Retention: Oman’s Perspective - Al- Awfi, Faisal; Hock, Oo Yu; Seenivasagam, Vasaki (2024)
This qualitative research explores the impact of technology on students' motivation and knowledge retention in Oman. With the increasing integration of digital tools and resources in educational settings, understanding how these technologies affect learning outcomes is crucial. The study employs semi-structured interviews and focus groups with students, teachers, and educational administrators from various schools and universities across Oman to gather in-depth insights. The findings suggest that technology, when effectively utilized, enhances student engagement and motivation by providing interactive and personalized learning experiences. However, challenges such as digital distraction, the quality of educational content, and varying levels of technological proficiency among both students and teachers were also identified. The study also reveals that while technology can support knowledge retention by offering diverse learning modalities and immediate feedback, its effectiveness heavily depends on the pedagogical strategies employed and the technological infrastructure available. This research provides valuable implications for educators and policymakers in Oman, highlighting the need for strategic implementation of technology in education to maximize its benefits for student motivation and learning retention. Future research could further explore specific technological tools or platforms and their differential impact on various learner demographics.